Magnetic Properties of Ferritchromite and Cr‐Magnetite and Monitoring of Cr‐Spinels Alteration in Ultramafic and Mafic Rocks. (5th November 2020) - Hodel, F.; Macouin, M.; Trindade, R. I. F.; Araujo, J. F. D. F.; Respaud, M.; Meunier, J. F.; Cassayre, L.; Rousse, S.; Drigo, L.; Schorne‐Pinto, J.
Abstract: Spinel is a ubiquitous mineral in mafic/ultramafic rocks. Spinel cores chemistry is extensively used as a petrogenetic proxy while their alteration phases, ferritchromite, and Cr‐magnetite, are used as metamorphic grade indicators. However, the magnetic properties and composition of these phases are still ill‐defined and no consensus exists concerning the metamorphic conditions involved in their formation. Here, we use the magnetic properties of these Cr‐spinel alteration phases, via field‐dependent parameters and observations with a magnetic microscope coupled with mineral chemistry and Mössbauer spectroscopy, to better constrain their composition. We identify Cr‐magnetite by a Curie point of ca. 520°C. We show that it is characterized by an n between 0.1 and 0.2 in the Fe‐Cr spinel formula [Fe 2+ (Fe1− n Cr n )2 O4 ], which corresponds to 6–13 wt.% of Cr2 O3 . The abundance of Cr‐magnetite indicates a strong alteration of Cr‐spinels that could reflect a significant hydrothermal activity rather than a high metamorphism grade. Normalized variation curves of the magnetic susceptibility during heating allow a relative quantification of the contributions of different magnetic phases to the magnetic susceptibility. This highlights a link between ferritchromite destabilization into maghemite at ca. 130°C followed by the destabilization of this maghemite starting at 300°C. We identify specific covariation trends between these two magnetic species characterizing different alteration processes. This study opens the door to magnetic monitoring of the Cr‐spinel alteration state in mafic and ultramafic rocks. It constitutes a new, fast, and weakly destructive way to study the petrological history of both terrestrial and extraterrestrial rocks. Plain Language Summary: Spinels are a common accessory mineral in Earth's mantle rocks, basaltic lavas and more generally, in mafic/ultramafic rocks from other telluric bodies. Because they are often (partially) preserved even in the case of highly altered rocks like serpentinites, and their chemistry is dependent on magmatic and metamorphic processes, they have been used for decades to investigate the history of their host rock. In this study, we focus on the magnetic and chemical characterization of the phases that compose spinel alteration rims, namely the ferritchromite and the Cr‐magnetite (Chromium‐rich magnetite). Coupling the magnetism and mineral chemistry methods allowed us to better constrain the magnetic behavior of these mineral phases, hence defining clear magnetic signatures for them and precise their chemical composition fields. We show that magnetic measurements can be used to finely monitor the spinels alteration state by quantifying the relative contributions of their different alteration products to the magnetization of a given rock sample. This constitutes a new way to study the metamorphic and/or hydrothermal history of both terrestrial and extraterrestrial rocks. Key Points: Main spinel alteration products can be easily identified via thermomagnetic measurements We redefine Cr‐magnetite as a Fe‐Cr spinel [Fe 2+ (Fe1− n Cr n )2 O4 ], with 0.1 < n < 0.2 (6–13 wt.% of Cr2 O3 ) and with a T c at ca. 500–530°C This study opens the door to magnetic monitoring of the Cr‐spinel alteration state in mafic and ultramafic rocks